Balance Scorecaed sebagai pengukuran kinerja pada PT. Bank X kantor cabang utama di wilayah jakarta utara - Ellen Oktaviane; steph Subanidja (Sekolah Pascasarjana Perbanas Jakarta, 2018)
The purpose of this research is to describe four perspectives on balance scorecard as performance measurement at PT Bank X Main Branch Office in North Jakarta Area. These four perspectives are financial perspective, customer perspective, internal business process perspective and growth and learning perspective. Based on the results of the analysis financial perspective fluctuating tends to decrease, the customer perspective fluctuating tend to decrease, the internal business processes perspective fluctuating tend to increase, the growth and learning perspective is very good. With this description, it is expected that the company can apply the balance scorecard in order to know the measurement performance of the bank as a whole which will then be improved or evaluated in order to be in accordance with the company's strategic objectives so as to advanced and maintain its presence in the banking industry. Keywords: Measurement Performance, Balance Scorecard